Highly Variable and Non-complex Diazotroph Communities in Corals From Ambient and High CO2 Environments - Geissler, Laura; Meunier, Valentine; Rädecker, Nils; Perna, Gabriela; Rodolfo-Metalpa, Riccardo; Houlbrèque, Fanny; Voolstra, Christian R. (Frontiers in Marine Science, 2021)
The ecological success of corals depends on their association with microalgae and a diverse bacterial assemblage. Ocean acidification (OA), among other stressors, threatens to impair host-microbial metabolic interactions that underlie coral holobiont functioning. Volcanic CO2 seeps offer a unique opportunity to study the effects of OA in natural reef settings and provide insight into the long-term adaptations under a low pH environment. Here we compared nitrogen-fixing bacteria (diazotrophs) associated with four coral species (Pocillopora damicornis, Galaxea fascicularis, Acropora secale, and Porites rus) collected from CO2 seeps at Tutum Bay (Papua New Guinea) with those from a nearby ambient CO2 site using nifH amplicon sequencing to characterize the effects of seawater pH on bacterial communities and nitrogen cycling. Diazotroph communities were of generally low diversity across all coral species and for both sampling sites. Out of a total of 25 identified diazotroph taxa, 14 were associated with P. damicornis, of which 9 were shared across coral species. None of the diazotroph taxa, however, were consistently found across all coral species or across all samples within a species pointing to a high degree of diazotroph community variability. Rather, the majority of sampled colonies were dominated by one or two diazotroph taxa of high relative abundance. Pocillopora damicornis and Galaxea fascicularis that were sampled in both environments showed contrasting community assemblages between sites. In P. damicornis, Gammaproteobacteria and Cyanobacteria were prevalent under ambient pCO2, while a single member of the family Rhodobacteraceae was present at high relative abundance at the high pCO2 site. Conversely, in G. fascicularis diazotroph communities were indifferent between both sites. Diazotroph community changes in response to OA seem thus variable within as well as between host species, potentially arguing for haphazard diazotroph community assembly. This warrants further research into the underlying factors structuring diazotroph community assemblages and their functional role in the coral holobiont.